Challenges and opportunities for ecotourism development: A case study in dilla university botanical and ecotourism garden, South Ethiopia - Israel Petros Menbere; Firew Admassu (Global Journal of Ecology - Peertechz Publications, 2020)
Dilla University Botanical and Ecotourism Garden was established in 2017 for the purpose of biodiversity conservation and ecotourism in Dilla area. This study was conducted to determine the opportunities and challenges for ecotourism development in the garden. Respondents from Odaya kebele, and key informants from government offices, Saron lodge, Dilla University, local elders and youth unions were selected for this study. Data were collected through questionnaires, interviews, focused group discussions and field visits. The study of community attitude towards ecotourism and the garden indicated as the majority of respondents were familiar with ecotourism and support its implementation in the garden. In addition, the present study revealed flora and fauna, attractive landscape, cultural resources and rivers as the main ecotourism attractions in the garden while diversity of ecotourism attractions, the unique natural and agro-forestry ecosystems of the Gedeo Zone, presence of different cultural attractions and existence of Saron Lodge in proximity to the garden as the top four opportunities to promote ecotourism in the area. As to the result of this study, the low level community benefit, inadequate community participation, absence of ecotourism plan and unsustainable use of resources were the major challenges of ecotourism development in the garden. The study also identified absence of sufficient accommodation and lack of local guides as first and second facility problems in the garden. To address the different problems and implement an integrated ecotourism development approach, involving communities and enhancing their role has been recommended as the key component of ecotourism development in the area.